Ancient Democracy Revisited by Gender Studies: the Abduction of Female Citizens in the Historiography of Classical Athens - Bacelar, Agatha Pitombo; Pio, Fernanda Israel; Leite, Lettícia (Revista Archai, 2024)
In this article, we investigate the impact of including the gender category, articulated with a decolonial perspective, in analyzing Athenian citizenship, especially in democratic classical Athens. Contrary to the traditional notion that views the polis as a "men's club," heavily influenced by certain works on Aristotle’s writings on citizenship, recent readings emphasize the explicit presence of women citizens in ancient Hellenic societies. By centering the debate on aspects linked to the ancient context and by paying attention to the projection of modern references, we propose a broader reflection on political practices in antiquity. Contemporary studies have revealed that ancient Greek citizenship was not based on systematically excluding women from all contexts. Free women citizens are mentioned and represented in the remains of ancient Hellenic societies. The persistence of the "men's club" stereotype in ancient politics is questioned, with an emphasis on the importance of religion in the civic context, where women play active roles. We inquire about the contemporary interest in perpetuating the view of the polis as an exclusively male arena and how this perception affects the understanding of women's participation in the political scene. We conclude by highlighting the importance of revisiting ancient texts from a contemporary critical perspective, feminist and decolonial, challenging the idea that women have always been on the sidelines of politics.